Penerapan Akad Rahn dalam Transaksi Gadai Lahan Pertanian Menurut Perspektif Ekonomi Islam (Studi pada Desa Tanjung Agung Kecamatan Ulu Musi Kabupaten Empat Lawang) - Wina Afrika; Idwal B; Uswatun Hasanah (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This study aims to examine the implementation of the rahn (pledge) contract in agricultural land pawn transactions in Tanjung Agung Village, Ulu Musi District, Empat Lawang Regency. The background of this research is based on the fact that the practice of pawning agricultural land in the village is still carried out informally, mostly through verbal agreements and mutual trust. This research uses a qualitative method with data collection techniques consisting of observation, interviews with 14 informants, and documentation. The results of the study indicate that the implementation of the rahn contract in Tanjung Agung Village has fulfilled the pillars and conditions of pledge in Islam, which include the pledger (rahin), the pledgee (murtahin), the pledged asset in the form of agricultural land, a clear amount of debt, and the sighat (offer and acceptance), although most transactions are conducted without written documentation. During the pawn period, the land is fully managed by the pledgee, and the harvest becomes their right. From the perspective of Islamic economics, this practice is generally in accordance with sharia principles as it is based on mutual consent between both parties, although it still has weaknesses in terms of documentation and legal protection. The study recommends the need for written agreements and the involvement of witnesses or village authorities to minimize the risk of disputes